Konsep Nasionalisme Abdurrahman Wahid Dan Implikasinya Dalam Pendidikan Islam Pada Era Revolusi Industri 4.0 - Nanang Abdillah; Lilik Husniah (Jurnal Pendidikan Agama Islam Miazhar, 2025)
The dynamics of the development of Islamic education in Indonesia reflect civilization, particularly the important issue of educational diversity, which must be implemented in the daily lives of students. The role of Islamic education is essential for preserving, maintaining, passing down to future generations, and continuing beliefs and traditions. The concept of nationalism has become one of the effective strategies for the existence of Islamic education development in Indonesia. This research was conducted to understand Abdurrahman Wahid's concept of nationalism and then analyze its implications in Islamic education during the 4.0 industrial revolution era. This research uses library research, which contains theories relevant to the research problems. The research method used is the qualitative research method. The research results show that: (1) The concept of nationalism from the perspective of KH. Abdurrahman Wahid is pluralism that must be embraced rather than merely tolerated, such as diversity in various aspects of justice; democracy based on three main principles, namely freedom, justice, and deliberation; humanism as a way of viewing humanity not as a mere collection of individuals but as a whole that has a place in the realm of God, in the realm of law, and does not discriminate between one and another. (2) The implications of the concept of nationalism from the perspective of KH. Abdurrahman Wahid in Islamic education during the era of the industrial revolution 4.0, namely Neo-Modernism-based Islamic education, which synthesizes two types of education: classical Islamic education and modern Western education, without forgetting the essence of Islamic teachings; liberation-based Islamic education that frees individuals or students from traditional shackles, which are then reprocessed by critically examining educational thoughts born from modern Western influences; multiculturalism-based Islamic education that fosters a high sense of tolerance and appreciation for differences among people, especially in the highly pluralistic context of Indonesia.